Fish scales patterning guiding hASC growth - Silva, Joana M. (2012)
Marine organisms and materials exhibit interesting properties for their use in biomedical applications, following biomimetic approaches [1,2]. For instance, the white seabass (Lates Calcarifer) scales exhibit a very interesting pattern, which inspire their use as a guiding platform for cellular growth, in a tissue regeneration approach. Moreover, fish scales are composed of hydroxyapatite and type I collagen fibrils, equivalent to the materials that one can find in human bone, as thus their use in bone tissue engineering is envisaged. The main goal of the present work was the assessment of fish scales, combining intrinsic features such as patterns, hydroxyapatite and collagen in different means, as cell culture supports aiming at guiding cell growth and extracellular matrix deposition and mineralization. In this sense, human adipose derived stem cells (hASCs) were cultured onto seabass scales, under osteogenic and non-osteogenic conditions. Fish scales supported cell adhesion and cytoskeleton organization defined by the surface patterning. Moreover, hASCs were able to proliferate along the time of culture and to differentiate towards the osteogenic lineage depositing and mineralizing the characteristic extracellular matrix. This work constitutes the first step to demonstrate the value of the intrinsic properties of seabass scales for exploitation in the biomedical field and in particular for bone tissue engineering.